Role of impurities in GaAs affecting the quantisation of electrons passage through island in single electron transistor. (1st October 2009) - Abdalla, S.; El-Shirbeeny, W.
We show that the presence of inevitable impurities in the semi-insulating GaAs domains when manufacturing a single electron transistor (SET) alters the quantisation mechanism of the single electron tunnelling through its course inside the island. Moreover, these impurities affect the amount of energy needed to change the number of electrons on the island. This decreases drastically the quality of the SET. The published experimental data (I-V characteristics) of GaAs nano-crystals has been well fitted to our model.